Relative sea-level and paleoenvironmental changes during the holocene in Southwest Bohol - Berdin, Rose Dycoco (2001)
Excellent sea-level indicators of the southwest coast of Bohol document Holocene changes in relative sea level, the response of paleoenvironments, specifically that of mangroves, and the possible role of tectonism in affecting these fluctuations. Sediment-core, tidal-notch and ¹⁴C data from the lower reaches of the Abathan River document a local Holocene eustatic sea-level trend that conformed to that of the far-field region: A rapid rise followed by a relative stillstand and a subsequent fall to the present. After the rapid early Holocene sea-level rise, a lagoon was formed and sebsequently filled. During the final stage of this infilling ca. 6000 yBP, while sea-level was rising more gradually, mangroves colonized the coast. Subsequently, however, ca. 4500 yBP, another rapid sea-level rise of 1.7 m, to 0.7 m above the present mean sea level, drowned the mangroves. This highstand lasted until ca. 2500 yBP, after which sea level fell 0.7 m to its present position. A broad, shallow basin created during this gradual fall allowed extensive reintroduction of mangroves. An almost continuous tidal notch around Panglao Island south of the Abatan River mouth indicates minor tectonic contributions to the sea-level changes. The tidal notch documents higher-than-present mean sea level, consistent with regional field observations and hindcasting for mid-Holocene time; however, lateral variations in notch elevations suggests differential tilting of the island. Moreover, these tidal-notch data, although indicating overall southwestward titling, vary in magnitude between several blocks, suggesting the presence of faults, which are corroborated by lineaments in aerial photographs and topographic maps. Augmented with data from previous work on the Late Pleistocene sea-level changes in the island, these variations in paleo-mean sea levels indicate differential land movements at least since the Last Interglacial. Rates of uplift are estimated at 0.03 and 0.006 m/100 y respectively for the Holocene and Late Pleistocene, implying that vertically, Panglao is relatively stable. After accounting for tectonic tilting, mid-Holocene sea level is estimated at approximately 0.3 m to 0.6 m. Tectonism contributing only minimally to relative sea-level changes in the study area indicates that the reconstructed sea levels are mainly eustatic. Thus, southwest Bohol can serve as a reference site for future sea-level studies.